The Influence of Promotion Intensity toward the Increasing of Rice Selling at Sulselbar Regional Division of Bulog Company In Makassar - Allamah Al Hasanah; Muhammad Guntur; Aris Baharuddin (Universitas Negeri Makassar, 2020)
Promotion Intensity Influence Toward The Increasing Of Rice Selling At Sulselbar Regional Division Of Bulog Company In Makassar. This research was conducted to know the promotion intensity influence toward the increasing of rice selling. Independent variable in this research was the promotion intensity and dependent variable was the increasing of rice selling at Sulselbar Regional Division of Bulog Company in Makassar. The sample in this study was Bulog partner, namely Sahabat RPK (Rumah Pangan Kita) or Our Home Food. Total number of the partners was 152 people and all of them applied Slovin sample theory. Data analysis in this research used SPSS 25 and for technique analysis, the researcher chose reliability test, validity test, classical assumption test, and inferential statistical analysis.The result of this research showed that in promotion intensity variable (X) indicated a very good trend for each indicator. Furthermore, the sales variable (y) showed a very good percentage and there was a significant influence between the intensity of promotion on the increasing of rice selling. It was proven by the result of coefficient analysis with a significance value of 0.000 < 0.05 and also the coefficient of determination (R2) 0.504 or 50.4 percent which indicated that the coefficient of determination model was good and has a positive correlation.